2020
DOI: 10.5194/essd-2020-117
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Dielectric database of organic Arctic soils (DDOAS)

Abstract: Abstract. This article presents a Dielectric database of organic Arctic soils (DDOAS). The DDOAS was created based on dielectric measurements of seven samples of organic-rich soils collected in various parts of the Arctic tundra: Yamal and Taimyr Peninsula, Samoilovsky Island (the Russian Federation), and Northern Slope of Alaska (U.S.). The organic matter content (by weight) of the soil samples presented varied from 35 % to 90 %. The refractive index (RI) and normalized attenuation coefficient (NAC) were meas… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…4) showed that A and B used in the quadratic function computed for SMAPVEX12 can be parameterized with soil texture, wilting point, porosity, and the bound and free water dielectric constants. Additionally, the C parameter indicates the effective dielectric constant of the mixture of dry organic matter (approximately 1.2; Savin et al, 2020) and solid mineral soil (3-5); ideally, the C parameter value should decrease with an increase in OC. Notably, the clay content was also positively correlated with an increase in OC in SMAPVEX12.…”
Section: Calibration Of Portable Soil Moisture Sensorsmentioning
confidence: 99%
“…4) showed that A and B used in the quadratic function computed for SMAPVEX12 can be parameterized with soil texture, wilting point, porosity, and the bound and free water dielectric constants. Additionally, the C parameter indicates the effective dielectric constant of the mixture of dry organic matter (approximately 1.2; Savin et al, 2020) and solid mineral soil (3-5); ideally, the C parameter value should decrease with an increase in OC. Notably, the clay content was also positively correlated with an increase in OC in SMAPVEX12.…”
Section: Calibration Of Portable Soil Moisture Sensorsmentioning
confidence: 99%